A preliminary study of cinemagraphas a tool in enhancing Public Service Announcement (PSA) on smoking habit issue / Fahmi Samsudin, Rosita Mohd Tajuddin and Nik Ridzuan Nik Yusoff - Fahmi, Samsudin; Rosita, Mohd Tajuddin; Nik Ridzuan, Nik Yusoff (2015)
Cinemagraph is a high definition new type of visual media that lies in between photos and videos where some parts that want to be highlight are animated and loop seamlessly while others remain completely still. Besides, this would serve as the future of new communication through social media by delivering contents in interactive way. Objectively, the point is to introduce the technique in creative industry in Malaysia at a new platform, thus this would give new breath in the related industry. Following this, this serves as a new hybrid image technology by replacing the current poster advertisements in the production phase where the process of printing and making the poster by machines is abolished, because of the technology is replaced by the place through electronic system. Results from the pilot test demonstrate that the self-designed measure is a very much reliable instrument, with an overall Cronbach alpha value of .93. Three factors emerge with high reliability scores of .70 and above. The correlation analysis demonstrates that the entire three dimensions are not perfectly correlated as their correlation analysis illustrates from low to moderate scores. Findings from the analysis confirm the reliability of the scale and validate the influenced results of the perception of public in predicting the existing of cinemagraph technique through the campaign. Results from the study demonstrate that the measurement used in the pilot study can serve as a potential measure in accessing the usability of Cinemagraph in Public service Announcement (PSA) campaign.